SEBUAH LAPORAN KASUS Sindrom Nefrotik pada Pasien Pengguna Obat Antiinflamasi Non Steroid (OAINS) pada Dewasa: sebuah Laporan Kasus - Mumtaza, Hilya Itsnain; Rochmah, Izzah (Jurnal Klinik dan Riset Kesehatan, 2023)
Background: Non-steroidal antiinflammatory drugs (NSAID) is a common drug with an antiinflammation and an analgesic effect which consumed widely among people. On the other hand, NSAID also have some adverse effects including nefrotic syndrome (NS). Case Presentation: A man, 20 years old, came with general body swelling. The swelling appeared gradually accompanied by shortness of breath as the body swelling was spread. The patient has a history of frequently consuming pain reliver medications which he bought over the counter, 3-4 times/week since 1 year ago. The patient was diagnosed with nephrotic syndrome. We stop the OAINS and administer some medications, such as, intravenous steroid, oral ARBs, and oral anticoagulant therapy. Patients responded well to the therapy given marked by reduced edema and improved kidney function. Discussion: NS is glomerular syndrome consists of massive proteinuria, hypoalbuminemia, peripheral oedema, and/or hyperlipidemia. The etiology of NS divided into 2 group : primary NS and secondary NS. The primary NS such as minimal change disease glomerulonephritis, membranous nephropathy, focal segmental glomerulonephritis, and IgA nephropathy. In the other hand, secondary SN can be caused by NSAID toxicity, infection, metabolic dysfunction, and autoimmune disease. Conclusion: In this case report, a male, 20 years old is diagnosed with NS and had medical history of being long term NSAID’s user who responded well after given steroid therapy. In order to find the definite etiology of SN, it need adjunct examination such as renal biopsy. Moreover, medical practitioner should do the holistic and comprehensive anamnesis and physical examination associated with the risk of NS.